BIOSYNTHESIS IN ISOLATED ACETABULARIA CHLOROPLASTS : I. Protein Amino Acids - Shephard, David C. (The Rockefeller University Press, 1972)
The ability of chloroplasts isolated from Acetabulana mediterranea to synthesize the protein amino acids has been investigated. When this chloroplast isolate was presented with (14)CO(2) for periods of 6–8 hr, tracer was found in essentially all amino acid species of their hydrolyzed protein Phenylalanine labeling was not detected, probably due to technical problems, and hydroxyproline labeling was not tested for The incorporation of (14)CO(2) into the amino acids is driven by light and, as indicated by the amount of radioactivity lost during ninhydrin decarboxylation on the chromatograms, the amino acids appear to be uniformly labeled. The amino acid labeling pattern of the isolate is similar to that found in plastids labeled with (14)CO(2) in vivo. The chloroplast isolate did not utilize detectable amounts of externally supplied amino acids in light or, with added adenosine triphosphate (ATP), in darkness. It is concluded that these chloroplasts are a tight cytoplasmic compartment that is independent in supplying the amino acids used for its own protein synthesis. These results are discussed in terms of the role of contaminants in the observed synthesis, the "normalcy" of Acetabularia chloroplasts, the synthetic pathways for amino acids in plastids, and the implications of these observations for cell compartmentation and chloroplast autonomy.